The Addition of Caulerpa racemosa Extract in Feed on Clinical Sign and Intestinal Histopathological Profile of Whiteleg Shrimp after Infected by Vibrio parahaemolyticus - Alvira Febrianti Pratiwi; Woro Hastuti Satyantini; Gunanti Mahasri; Akhmad Taufiq Mukti; Alim Isnansetyo (Department of Aquaculture, 2022)
The purpose of this study was to determine the administration of Caulerpa racemosa extract in clinical sign and intestinal histopathological profile of whiteleg shrimp (Litopenaeus vannamei) after infected by Vibrio parahaemolyticus. The study was conducted using a completely randomized design (CRD) with six treatments and three replications. Shrimp were divided into six groups, two control groups without the administration of C. racemosa extract, the other four groups with the administration of C. racemosa extract with successive doses; 30 mg/kg (P1), 60 mg/kg (P2), 120 mg/kg (P3) and 240 mg/kg (P4) through feed. On the 15th day of rearing, the control group was divided into two groups: negative control (K-) was injected with PBS and then positive control (K+) and four other treatments (P1, P2, P3 and P4) were infected with V. parahaemolyticus. The results showed that intestinal damage caused by V. parahaemolyticus infection were inflammation and necrosis. The administration of C. racemosa extract had a significant effect on the histopathological profile of the whiteleg shrimp intestine. The lowest percentage of damage was found in the P4 treatment, which was 19.6% with a indication of low damage. Clinical sigs appeared at 48 hours post-infection pale hepatopancreas, empty intestines, reddened uropods and gnats. From this study, it can be concluded that the administration of C. racemosa extract to the feed at a dose of 240 mg/kg is the best dose in reducing the level of damage to the intestinal organs of whiteleg shrimp infected with V. parahaemolyticus.